Future of Sustainable Agriculture in Saline Environments - Negacz, Katarzyna; Vellinga, Pier; Barrett-Lennard, Edward; Choukr-Allah, Redouane; Elzenga, Theo (Taylor & Francis, 2021)
Food production on present and future saline soils deserves the world's attention particularly because food security is a pressing issue, millions of hectares of degraded soils are available worldwide, freshwater is becoming increasingly scarce, and the global sea-level rise threatens food production in fertile coastal lowlands. Future of Sustainable Agriculture in Saline Environments aims to showcase the global potential of saline agriculture. The book covers the essential topics, such as policy and awareness, soil management, future crops, and genetic developments, all supplemented by case studies that show how this knowledge has been applied. It offers an overview of current research themes and practical cases focused on enhancing food production on saline lands. FEATURES Describes the critical role of the revitalization of salt-degraded lands in achieving sustainability in agriculture on a global scale Discusses practical solutions toward using drylands and delta areas threatened by salinity for sustainable food production Presents strategies for adaptation to climate change and sea-level rise through food production under saline conditions Addresses the diverse aspects of crop salt tolerance and microbiological associations Highlights the complex problem of salinity and waterlogging and safer management of poor-quality water, supplemented by case studies A PDF version of this book is available for free in Open Access at www.taylorfrancis.com. It has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.